2011
DOI: 10.1002/gps.2716
|View full text |Cite
|
Sign up to set email alerts
|

‘Doing things differently’—working towards distributed responsibility within memory assessment services

Abstract: In this study, structured initial assessment by AHP's working in a Memory Assessment Service was shown to be an accurate method of determining a diagnosis of cognitive impairment, when compared with formal MDT judgment. It is suggested that such distributed responsibility affords a viable option for the future detection of early dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Another emerging care model in the UK utilises the services of ‘allied mental health professionals’ in making diagnoses and offering interventions with medical input not provided face to face for most patients. 5 , 37 , 38 It may be argued that some of the diagnostic quality provided by a ‘medical’ view on diagnosis may be compromised in such services and this needs further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Another emerging care model in the UK utilises the services of ‘allied mental health professionals’ in making diagnoses and offering interventions with medical input not provided face to face for most patients. 5 , 37 , 38 It may be argued that some of the diagnostic quality provided by a ‘medical’ view on diagnosis may be compromised in such services and this needs further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous papers the possibility of clinical responsibility being more equitably distributed across the multidisciplinary team has been explored and we have demonstrated that higher levels of practice in respect of assessment and diagnosis making are achievable (Page et al . , ). However, these findings are based on two teams where either practitioners held higher than average postgraduate qualifications or had recently completed an intensive training programme.…”
Section: Introductionmentioning
confidence: 99%
“…They are more likely to rely on standardised protocols with inclusion/exclusion criteria designed to be risk-avoidant and limit workload rather than respond to patient need. 11 Lessons from the 10/66 studies and initiatives encourage the use of low-tech, clinically competent approaches with training and support to local healthcare agents. 12 , 13 …”
Section: Identifying Weakness In Existing Servicesmentioning
confidence: 99%